The Global Correspondence Principle: A Generalization - Bhagwati, Jagdish N.; Brecher, Richard A.; Hatta, Tatsuo (American Economic Review, 1987)
[This paper generalizes the Global Correspondence Principle by extending, in two major ways, Paul Samuelson's 1971 analysis of the exchange rate response to an international purchasing-power transfer. We analyze the price effect of a shift in any parameter, not necessarily a transfer. We then explore the resulting adjustments in any nonprice variable such as welfare. As our analysis shows, the direction of these adjustments depends neither on whether they are small or large nor on whether equilibrium is locally stable or unstable.]